Hydrophobic Outer Membrane Pores Boost Testosterone Hydroxylation by Cytochrome P450 BM3 Containing Cells - Bertelmann, Carolin; Mock, Magdalena; Koch, Rainhard; Schmid, Andreas; Bühler, Bruno (Frontiers in Catalysis, 2022)
The implementation of biocatalytic steroid hydroxylation processes at an industrial scale still suffers from low conversion rates. In this study, we selected variants of the self-sufficient cytochrome P450 monooxygenase BM3 from Bacillus megaterium (BM3) for the hydroxylation of testosterone either at the 2β- or 15β-position. Recombinant Escherichia coli cells were used as biocatalysts to provide a protective environment for recombinant enzymes and to ensure continuous cofactor recycling via glucose catabolism. However, only low initial whole-cell testosterone conversion rates were observed for resting cells. Results obtained with different biocatalyst formats (permeabilized cells, cell-free extracts, whole cells) indicated a limitation in substrate uptake, most likely due to the hydrophilic character of the outer membrane of Escherichia coli. Thus, we co-expressed nine genes encoding hydrophobic outer membrane proteins potentially facilitating steroid uptake. Indeed, the application of four candidates led to increased initial testosterone hydroxylation rates. Respective whole-cell biocatalysts even exceeded activities obtained with permeabilized cells or cell-free extracts. The highest activity of 34 U gCDW-1 was obtained for a strain containing the hydrophobic outer membrane protein AlkL from Pseudomonas putida GPo1 and the BM3 variant KSA14m. Overall, we show that the straightforward application of hydrophobic outer membrane pores can boost whole-cell steroid conversion rates and thus be game-changing with regard to industrial steroid production efficiency.